The role of INFL in code-switching: a study of a Papiamento heritage community in the Netherlands - Parafita Couto, M. Carmen; Pouw, Charlotte; Laanen, Rodi; López, Luis (Frontiers in Language Sciences, 2024)
Introduction In heritage bilingualism studies, code-switching has often been overlooked, with a focus on either the heritage language or the dominant societal language of the bilingual individual. However, exploring code-switching can provide valuable insights into heritage speakers' grammar, revealing patterns that may not be apparent when only examining monolingual speech. Recent research suggests that in code-switched clauses, functional elements must align with the language of verbal inflection (INFL), which encompasses tense, aspect, voice, and agreement. This generalization is usually referred to as the Matrix Language Frame (MLF). The present study explores the empirical validity of this generalization using an experimental protocol that controls for variables that earlier work did not take into consideration. These variables are (a) adjacency between INFL and the functional element, (b) the interaction of the MLF with embedded islands, and (c) the possibly degrading effects of inserting a functional category. Thus, the aim of this study is to provide evidence in support (or not) of the INFL constraint beyond the experimental limitations in earlier work. The study focuses on the bilingual combination Papiamento–Dutch. Our results, by and large, support the MLF generalization. Methods We carried out an online audio survey (3-point Likert scale) with 43 Papiamento–Dutch bilinguals. We manipulated the position of the switch and controlled for potential directionality effects by presenting code-switches in both switching directions. Results We find a scale of acceptability, where the conditions that respect the INFL constraint are preferred. Additionally, and consistent with recent corpus and experimental literature, our results point to a clear asymmetry regarding directionality effects or choice of ML, reflecting how code-switching is deployed in the community. Discussion Controlling for directionality allows us to discern the mechanisms of the INFL constraint. Thus, these findings underscore the intertwining influence of linguistic factors and community norms in guiding code-switching dynamics. Such insights extend beyond the specific context to shed light on broader dynamics within (heritage-language) bilingualism.